Public health preparedness and response synergies between institutional authorities and the community: a qualitative case study of emerging tick-borne diseases in Spain and the Netherlands - Daniel H. de Vries; John Kinsman; Anne Lia Cremers; John Angrén; Massimo Ciotti; Svetla Tsolova; Emma Wiltshire; Judit Takacs (BMC, 2021)
Abstract Background Communities affected by infectious disease outbreaks are increasingly recognised as partners with a significant role to play during public health emergencies. This paper reports on a qualitative case study of the interactions between affected communities and public health institutions prior to, during, and after two emerging tick-borne disease events in 2016: Crimean-Congo Haemorrhagic Fever in Spain, and Tick-Borne Encephalitis in the Netherlands. The aim of the paper is to identify pre-existing and emergent synergies between communities and authorities, and to highlight areas where synergies could be facilitated and enhanced in future outbreaks. Methods Documentary material provided background for a set of semi-structured interviews with experts working in both health and relevant non-health official institutions (13 and 21 individuals respectively in Spain and the Netherlands), and focus group discussions with representatives of affected communities (15 and 10 individuals respectively). Data from all sources were combined and analysed thematically, initially independently for each country and then for both countries together. Results Strong synergies were identified in tick surveillance activities in both countries, and the value of pre-existing networks of interest groups for preparedness and response activities was recognised. However, authorities also noted that there were hard-to-reach and potentially vulnerable groups, such as hikers, foreign tourists, and volunteers working in green areas. While the general population received preventive information about the two events, risk communication or other community engagement efforts were not seen as necessary specifically for these sub-groups. Post-event evaluations of community engagement activities during the two events were limited, so lessons learned were not well documented. Conclusions A set of good practices emerged from this study, that could be applied in these and other settings. They included the potential value of conducting stakeholder analyses of community actors with a stake in tick-borne or other zoonotic diseases; of utilising pre-existing stakeholder networks for information dissemination; and of monitoring community perceptions of any public health incident, including through social media. Efforts in the two countries to build on the community engagement activities that are already in place could contribute to better preparedness planning and more efficient and timely responses in future outbreaks.